Indigenous Knowledge Governance Framework : Scaffolding Joint ICT Developments in Long Lamai, Malaysia - Narayanan, A/L N. Kulathu Ramaiyer; Tariq, Zaman; Yeo, Alvin Wee (Informing Science Press, 2015)
Indigenous knowledge encompass generations of experimentation and innovation which has been carried over orally through the years and now serves communities as a rich source of tacit and implicit knowledge. This knowledge, which is deeply rooted in the social and cultural context of indigenous communities, can potentially be the key and inspiration to resolve many emerging complex problems. Indigenous knowledge is thus a time-tested hidden treasure of intellectual property, covering all aspects of our life and a basis for context-specific, task centric knowledge management.